Tourism Project Screening Approach in Environmental Impact Assessment in Vietnam - Thanh Tuong, Nguyen (Eco-Tourism and Sustainable Development, 2025)
In the context of the strong development of the tourism industry in Vietnam, tourism projects are increasingly expanding in scale and location, especially in environmentally sensitive areas such as special-use forests, coastal areas and nature reserves. Although they contribute greatly to economic growth and employment, these projects also pose many risks of causing negative impacts on the environment and society. Environmental impact assessment (EIA) is an important management tool to identify and control such impacts. Screening is the first and very important step to help determine whether a project requires an EIA or not, bringing many benefits in terms of efficiency and environmental management. However, current project screening is still done in a formal and ineffective manner, leading to impractical EIA reports that do not focus on core issues. This study focuses on analyzing the role, current status and limitations of the screening step in EIA of tourism projects in Vietnam, and proposes a new, flexible approach, combining qualitative and quantitative methods, to improve the quality and effectiveness of this step. The proposed 6-step screening process helps to identify major impacts early, save resources and increase transparency in decision-making. The study also recommends improving the legal framework, enhancing staff training, applying technology and promoting the role of the community in monitoring and feedback. This is an important basis for improving the quality of EIA and moving towards sustainable tourism development.